Estrogen receptors α and β and progesterone receptors in normal bovine ovarian follicles and cystic ovarian disease - Salvetti, Natalia R. (2007)
The purpose of this study was to determine by immunohistochemistry the expression of estrogen and progesterone receptors in ovarian follicular structures from cows with cystic ovarian disease (COD) and to compare these with normal ovarian structures. Secondary, tertiary, atretic, and cystic follicles were evaluated. The follicular cysts of animals with COD presented a significantly higher expression of estrogen receptor a in all follicular layers than secondary, tertiary, and atretic follicles in both groups (P < .05). The intensity of estrogen receptor β in the granulosa cell layer was stronger in tertiary than in secondary and atretic follicles in normal animals (P < .05) and in growing and cystic follicles in animals with COD (P < .05). Theca cells were scarcely stained in the 2 groups. Growing follicles and cysts from COD animals were less stained than tertiary follicles from normal animals (P < .05). Differences did not exist between the 2 groups with regard to the progesterone receptor. Ovaries of animals with COD exhibited altered estrogen receptors expression compared with that in normal animals.